Use of topical corticost eroids in dermatological conditions: data from real world - Nott, Anand; Sakhiya, Jagadish; Sharma, Richa; Aich, Biswajit; Muchhala, Snehal Sameer; Katare, Sagar; Sanghavi, Arti; Reddy, B. Swathi; Kotak, Bhavesh P.; Pitalia, Shraddha; Gudibanda, Sandeep; Govindaraj, Jayanthy (International Journal of Research in Dermatology, 2024)
Background: Topical corticosteroids (TCS) are the first treatment option prescribed for various dermatologic conditions. When used as monotherapy or combination therapy, TCS can efficiently alleviate the symptoms of atopic dermatitis and psoriasis. This electronic medical records (EMR) based study was planned to evaluate the TCS usage pattern in atopic dermatitis and psoriasis. Methods: This was a real-world, retrospective, cross-sectional, EMR-based study where anonymized data of patients diagnosed with psoriasis (≥18 years) or atopic dermatitis (all age groups) and prescribed with TCS from 2017-2023 was extracted from the EMR database for analysis. Demographic characteristics of patients (age, gender), duration of the TCS prescribed, comorbid conditions and the concomitant medications prescribed with TCS were evaluated. Results: Monotherapy (single TCS) was the most preferred. Clobetasol propionate, mometasone furoate and desonide were commonly prescribed. For psoriasis, a combination of TCS with non-steroidal molecules was most preferred. The most prescribed was the fixed-dose combination (FDC) of clobetasol propionate and salicylic acid. Antihistamines and emollients were the most common concomitant medications prescribed for atopic dermatitis patients. Antihistamines and immunosuppressants were the commonly prescribed concomitant medications for psoriasis patients. Conclusions: It can be inferred from the findings of the study that TCS remain the mainstay for the treatment of atopic dermatitis and psoriasis. TCS monotherapy was preferred for atopic dermatitis while combination therapy emerged as the preferred approach for psoriasis patients.